Public Relations Techniques / Second Edition Extensively Revised and Updated for the 1990s - Jefkins Frank (Butterworth Heinemann, 1994)
A comprehensive picture of the role of public relations in commercial and non-commercial organizations. Preface, Acknowledgements, Planning and Management, Media Relations, The Media of Communication, Special Areas of Public Relations, Index.